Conduction Velocity of Muscle Action Potential of Knee Extensor Muscle During Evoked and Voluntary Contractions After Exhaustive Leg Pedaling Exercise - Watanabe, Kohei; Sakai, Taiki; Kato, Shosaku; Hashizume, Natsuka; Horii, Naoki; Yoshikawa, Maki; Hasegawa, Natsuki; Iemitsu, Keiko; Tsuji, Katsunori; Uchida, Masakata; Kanamori, Masao; Iemitsu, Motoyuki (Frontiers in Physiology, 2020)
Purpose Conduction velocity of muscle action potential (CV) has been developed to estimate neuromuscular fatigue and measured during voluntary (VC) and electrically evoked (EC) contractions. Since CV during VC and EC reflect different physiological phenomena, the two parameters would show inconsistent changes under the conditions of neuromuscular fatigue. We investigated the time-course changes of CV during EC and VC after fatiguing exercise. Methods In 14 young males, maximal voluntary contraction (MVC) of knee extensor muscles, CV during electrical stimulation (CV-EC) and MVC (CV-VC) were measured before and immediately, 30 min, 60 min, 120 min, and 24 h after exhaustive leg pedaling exercise. Results CV-EC significantly increased immediately after the fatiguing exercise (p < 0.05) and had a significant negative correlation with MVC in merged data from all time-periods (r = -0.511, p < 0.001). CV-VC significantly decreased 30, 60, and 120 min after the fatiguing exercise (p < 0.05) and did not show any correlations with MVC (p > 0.05). Conclusion These results suggest that CV during EC and VC exhibits different time-course changes, and that CV during EC may be appropriate to estimate the degree of neuromuscular fatigue after fatiguing pedaling exercise.